Guidelines for Enhancing the Effective Management of Hotel Enterprises - KOBYAK, Marina Viktorovna; LAYKO, Mikhail Yurevich (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The article deals with the guidelines for enhancing the effective management of hotel enterprises The author suggested methodological approaches to assessing the competitiveness of hotel enterprises’ services, the choice of strategic development alternatives based on the analysis of the competitive position of a hotel enterprise in the hospitality industry, as well as the method of forming a rational pricing policy of a hotel enterprise based on the classifier of the hotel services market.
Keywords: efficiency, management, hotel, methods, competitiveness, service, pricing policy, market of hotel services